Diabetes and Cancer Associated Complications - Singh , Vinita (Socio-Scientific Interaction in Diabetes and Cancer and Its Management, 2023)
Diabetes and cancer are most prevalent chronic diseases worldwide. Studies have shown that there is a strong association between diabetes and an increased risk of cancer, as well as of mortality. The purpose of this review article is to be aware means the risk of association between diabetes and cancer and the steps to prevent it by medication and other because studies still obscure whether diabetes leads to cancer or cancer causes diabetes.